The John Insall Award: No Functional Benefit After Unicompartmental Knee Arthroplasty Performed With Patient‐specific Instrumentation: A Randomized Trial. Issue 1 (January 2016) - Ollivier, Matthieu; Parratte, Sebastien; Lunebourg, Alexandre; Viehweger, Elke; Argenson, Jean‐Noel
Abstract: Background: Component alignment can influence implant longevity as well as perhaps pain and function after unicompartmental knee arthroplasty (UKA), but correct alignment is not consistently achieved. To increase the likelihood that good alignment will be achieved during surgery, smart tools such as robotics or patient‐specific instrumentation (PSI) have been introduced. Questions/purposes: We hypothesized that UKA performed with PSI would result in improved level gait as ascertained with three‐dimensional analysis, implant positioning, and patient‐reported outcomes measured by a validated scoring system when compared with conventional instrumentation 3 months and 1 year after surgery. Methods: We randomized 60 patients into two groups using either the PSI technique or a conventional technique. All patients were operated on using the same technique and the same cemented metal‐backed implant. Mean age of the patients was 63 ± 4 years (range, 54‐72 years) and mean body mass index was 28 ± 3 kg/m 2 . Patients were evaluated preoperatively, at 3 months, and 1 year after surgery by an independent observer blind to the type of technique. Gait parameters were assessed with three‐dimensional analysis during level walking preoperatively and at 1 year, frontal and sagittal position of the implant was evaluated on full‐length radiographs at 3 months, and subjective functional outcome and quality of life using routine questionnaires (SF‐12, new Knee Society Score [KSS], Knee Injury and Osteoarthritis Outcome Score) at 3 months and 1 year. This study had 80% power to detect a 15% difference in walking speed at the p < 0.05 level. Results: One year after surgery, there were no differences between the two groups in the analyzed gait spatiotemporal parameters, respectively, for PSI UKA and conventional UKA: double limb support 31% (25%‐54%) versus 30% (23%‐56%; p = 0.67) and walking speed (1.59 m/s [0.86‐1.87 m/s] versus 1.57 m/s [0.71‐1.96 m/s]; p = 0.41). No difference was observed between the two groups in terms of lower limb alignment (PSI group 178° ± 3°, conventional group 178° ± 4°; p = 0.24) or implant positioning on mediolateral and anteroposterior radiographs. There were no differences in the functional score between the PSI and conventional TKA groups at 3 months and 1 year after surgery: KSS objective knee scores (PSI: 85 ± 8 points at 3 months, 87 ± 5 points at 1 year and conventional instrumentation: 82 ± 8 points at 3 months 83 ± 6 points at 1 year; p = 0.10) and functional activity scores were similar in both group (PSI: 71 ± 12 points at 3 months and 74 ± 7 points at 1 year versus conventional group: 73 ± 11 points at 3 months and 75 ± 6 at 1 year; p = 0.9). Conclusions: Our observations suggest that PSI may confer small, if any, advantage in alignment, pain, or function after UKA. This argument can therefore not be used to justify the extra cost and uncertainty related to this technique. Level of Evidence: Level I, therapeutic study.